Experimental Investigation of Thermal Conductivity and Electrical Conductivity of BioGlycol - Water Mixture Based Al2O3 Nanofluid - M. Kh., Abdolbaqi; Azmi, W. H.; R., Mamat; K. V., Sharma; G., Najafi (Elsevier Ltd, 2016)
Nanofluid as a new brand of cooling fluid consisting of nanometer-sized particles dispersed in base fluid. In this study, the thermal conductivity and electrical conductivity of BioGlycol (BG)–water (W) mixed nanofluids containing Al2O3 nanoparticles were studied. Nanofluids with 0.5 to 2.0% concentrations were prepared by the two-step method. The nanofluids demonstrated excellent stability over the temperature range of 30 to 80 °C after using the long term sonication process. Comparisons of the experimental data with many existing models illustrated that they do not display good agreement. Therefore, a new nonlinear model has been developed with 5% maximum deviation for the thermal conductivity of nanofluids as a function of temperature and volume concentration. The results of BG:W mixtures have displayed improvement in thermal performance of 7.5% in comparison with Propylene glycol (PG):W in similar circumstances. The thermal conductivity of nanofluid increased as a function of volume concentration and temperature. The maximum thermal conductivity enhancement using 40:60% (BG:W) mixture ratio was twice as high as 60:40% in the same conditions. Electrical conductivity was observed to decrease as the volume concentration increased. Thermo-electrical conductivity ratio (TEC) has been evaluated theoretically based on thermal and electrical conductivity results.